Ḵẖṳtbāt-i Sayyidu : Bazm-i Ṣūfiyā-yi Sindhu je mauq ʻuni te Jī.Em. Sayyidu ʻain ̤biyan jūn kayala taqrīrūn ʻain kārguzāriyūn - Sayyidu, Jī. Em., 1904- (Naʼīn Sindhu Pablīkeshani, 1975)
Speeches delivered by the author at various Sind Cultural Conferences held during 1916-1969; includes a few speeches by others.